The Development Of A Contextual Based Yoga Learning Model (Pybk) In Physical, Sport And Health Education (Pjok) Subject - I Wayan Muliarta, James Tangkudung, Moh. Asmawi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The objective of this study was to develop a contextual based yoga model. The type of this study was R&D development with the chosen development design model referring to the development proposed by Borg and Gall. The subjects of this study were students of grade 8 in Physical, Sport, and Health Education (PJOK) subjects. The types of data collection were interviews and questionnaires. Based on the results of the study, the development of the PYBK model had met the operating criteria of a learning model, namely: syntax, social system, principles of reaction, support system, instructional impact, and nurturant effects), and the resulting PYBK model had met the validity, practicality, and effectiveness requirements, namely (a) model validity, in expert testing 100% the validator states that the PYBK model is based on the strong theory, and all validators (100% ) states that the components of the model are closely related. Both the results of small group trials and field tests of 100% validators state that the PYBK model is based on strong theory and the components of the model are interrelated, (b) the practicality of the model, in expert testing more than 50% of the validators state that the PYBK model can be applied in class, and the teacher states that they can apply this learning model in the classroom. (c) the effectiveness of the PYBK model, from the results of the trial which can be seen from student activities, learning outcomes, and student responses to the implementation of the PYBK model meets all the requirements where student learning activities are classified as very high/very active category, the average of student learning outcomes are classified as good and very good with a Minimum Completeness Criteria (KKM) percentage ? 85%. Thus, it can be said that the PYBK model is successfully developed and it has a positive impact on the learning-teaching process.